2022
DOI: 10.1136/bmjopen-2022-064284
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with poor medication adherence during COVID-19 pandemic among hypertensive patients visiting public hospitals in Eastern Ethiopia: a cross-sectional study

Abstract: ObjectiveThis study aimed to assess factors associated with poor medication adherence during the COVID-19 pandemic among hypertensive patients visiting public hospitals in Eastern Ethiopia.SettingHospital-based cross-sectional study was conducted in Harari regional state and Dire Dawa Administration from 1 January to 30 February 2022. Both settings are found in Eastern Ethiopia.ParticipantsA total of 402 adult hypertensive patients who visited the chronic diseases clinic for follow-up were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Among this, 14 studies focused on chronic disease patients, five focused on diabetes, three focused on hypertension, two focused on diseases and/ or hypertension, one focused on cancer, and one focused on cardiovascular disease. The review findings were organized into five frequently reported themes and subthemes: these are 1) disruption of follow-up care and poor health care utilization reported by 11 studies [10,11, 23,24,25,26,27,28,29,30,31]; 2) increased anxiety, stress, depression, and increased mental health problems reported by eight studies [15,32, 34,35,37,38,39,43]; 3) substance use reported by four studies [36,37,41,44]; 4) decreased physical activity and sedentary life reported by three studies [33,36,44]; and 5) increased food insecurity and poor dietary habits due to COVID-19 among NCDs patients, reported in five studies [36,40,42,43,44] Studies included in this review did not focus on the same subject matter. Some studies focused on one theme and others focus on more than two themes; for instance, (Andualem et al, 2020) examined adherence to lifestyle modifications and reported on diet, exercise, smoking, and alcohol, whereas (Abate et al, 2022) examined adherence to physical exercise recommendations and reported only on exercise compliance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among this, 14 studies focused on chronic disease patients, five focused on diabetes, three focused on hypertension, two focused on diseases and/ or hypertension, one focused on cancer, and one focused on cardiovascular disease. The review findings were organized into five frequently reported themes and subthemes: these are 1) disruption of follow-up care and poor health care utilization reported by 11 studies [10,11, 23,24,25,26,27,28,29,30,31]; 2) increased anxiety, stress, depression, and increased mental health problems reported by eight studies [15,32, 34,35,37,38,39,43]; 3) substance use reported by four studies [36,37,41,44]; 4) decreased physical activity and sedentary life reported by three studies [33,36,44]; and 5) increased food insecurity and poor dietary habits due to COVID-19 among NCDs patients, reported in five studies [36,40,42,43,44] Studies included in this review did not focus on the same subject matter. Some studies focused on one theme and others focus on more than two themes; for instance, (Andualem et al, 2020) examined adherence to lifestyle modifications and reported on diet, exercise, smoking, and alcohol, whereas (Abate et al, 2022) examined adherence to physical exercise recommendations and reported only on exercise compliance.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of follow-up care and poor healthcare utilization in sub-Saharan Africa were the most frequently reported challenges reported by ten studies included in this systematic review [10,11, 23,24,25,26,27,28,29,30,31]. Some of the reasons for this disruption include fear of contracting COVID-19, transportation challenges, and limited access to healthcare facilities due to lockdowns and restrictions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study conducted during the COVID-19 pandemic established that the level of poor antihypertensive medication adherence was 63% and connected to several factors. Factors associated with poor medication adherence during COVID-19 were lack of formal education, existing comorbid conditions, poor knowledge about hyper-tension, poor patient-physician relationships, and unavailability of medication [ 26 ]. A study conducted in Turkey to assess blood pressure management and adherence to medication established that 58.7% had their blood pressure checked during the pandemic, while 15.5% changed their dosage or timing without doctors’ approval [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is important as there have been concerns with patient management across countries if there is limited access to treatment centers during the pandemic, and patients with T2DM are not being encouraged to continually improve their lifestyles as well as adhere to their prescribed medicines [ 22 , 45 , 46 , 55 , 56 , 57 ]. In addition, the high prevalence of uncontrolled T2DM and hypertension, as well as delays in the diagnosis of cardiovascular diseases among patients with diabetes before and during the pandemic, with its associated lockdown measures [ 29 , 30 , 31 , 32 ], further exacerbates concerns in this high-priority population [ 48 , 50 , 58 , 59 ]. We are aware that the pandemic has also adversely impacted on the diagnosis and management of other NCDs in LMICs [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%